Islamic and Western Education Systems – Perceptions of Selected Educationists in Malaysia - Muhammad Abid Ali (Journal of Education and Educational Development, 2020)
This research article explores the perceptions of Muslim educationistsin Malaysia about the Islamic and the western education systems.Views of two faculty members, who are active proponents of Islamiceducation, were acquired through interviews and their perceptionson Islamic and western education systems were analyzed and thencontrasted against the views of Dr. Syed Naquib al-Attas, who isconsidered to be one of the architectsof the project of Islamizationof knowledge and education.Qualitative exploratory methodologywas followed for this research, where the views of the two educationistswere analyzed using thematic analysis,and the views of Dr. Naquibal-Attas were derived through document analysis of his writings oneducation and finally contrasted.It was revealed that there existsa gap in the understanding of the depth of philosophical conceptsand issues of education between these educationists and Naquib al-Attas.
Keywords: Islamic education; Islamization of education; Islamization of knowledge; western education